Effect of a digital literacy through workshop training programs on older adults: a quasi-experimental study - Siriwattanarat, Ruthairat; Meethongjan, Kittikhun; Charoensuk, Ornuma; Tsailexthim, Donsak; Wongroj, Weerawich (International Journal of Evaluation and Research in Education (IJERE), 2025)
In Bangkok, Thailand, workshop training programs aimed at enhancing digital literacy among older adults have been developed. The objective of this study was to assess whether a structured digital literacy workshop could improve mobile device proficiency among older adults in Bangkok. This program consisted of six workshops focusing on mobile devices such as smartphones or tablets. This quasi-experimental study investigates the impact of these workshops on digital device usage among urban community adults aged 60 and above. Digital literacy was assessed using the mobile device proficiency questionnaire (MDPQ-16) at three stages, they are baseline (pretest), immediately after program completion (post-intervention), and one month later (follow-up). A total of 84 older adults participated in these workshop training programs. Our findings indicate a significant increase in mobile device proficiency (P<.000). Participants showed substantial improvement in digital literacy at both the posttest and intervention assessments compared to pretest, with no significant difference observed between posttest and intervention scores. However, participants aged 70 and older with lower education levels demonstrated comparatively lower levels of digital literacy. These findings underscore the importance of implementing structured and accessible digital literacy training for older adults, particularly for those with lower educational attainment, to reduce digital disparities and promote inclusive access to essential digital services.